THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE WORK MOTIVATION IN KELURAHAN BUNGUR OFFICE CENTRAL JAKARTA - Nyoman Suardhita; Ahmad Rafik; ##grid.settings##Irwin Sukrisno Sugeng (Kusuma Negara Business School, 2019)
Leadership style influences work motivation because leadership style is right and is liked by employees, able to increase work motivation. The more employees who have motivation in working, the goals set by the company can be quickly implemented so that the company is able to survive in global competition. In this regard, the Central Jakarta Bungur Village Office is a government agency that is engaged in providing services to the community because the leadership style adopted by the leadership of the office can motivate employees to work and complete work effectively and efficiently. Data collection methods used in this study were observation, interviews, questionnaires, and documentation studies with quantitative research methods. Data obtained based on the results of the questionnaire distributed to 30 employee respondents at the Bungur district office in Central Jakarta and processed using SPSS 25 stated that the questionnaire was valid and reliable. Correlation coefficient test results of 0.740 and P-value 0.000 means there is a strong and significant relationship between leadership style on employee work motivation. The coefficient of determination test results shows the influence of leadership style on employee work motivation with a percentage of 54.8%. From the research results the formed regression coefficient is Y = 9,152 + 0.721 X.